2017
DOI: 10.1021/acssynbio.7b00128
|View full text |Cite
|
Sign up to set email alerts
|

Development of Artificial Riboswitches for Monitoring of Naringenin In Vivo

Abstract: Microbial strains are considered promising hosts for production of flavonoids because of their rapid growth rate and suitability for large-scale manufacturing. However, productivity and titer of current recombinant strains still do not meet the requirements of industrial processes. Genetically encoded biosensors have been applied for high-throughput screening or dynamic regulation of biosynthetic pathways for enhancing the performance of microbial strains that produce valuable chemicals. Currently, few protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 52 publications
0
62
0
Order By: Relevance
“…In vitro and in vivo selections can then be performed to empirically validate each design in a high-throughput manner in an environment where the dynamic RNA controllers should work. The potential of empirical selection should be further explored because the quantitative properties of RNA controllers can be modulated using well-designed in vivo selection schemes [43 ]. Emerging approaches in the development of dynamic RNA controllers will expand the repertoire of genetic parts for applications in metabolic engineering and synthetic biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo selections can then be performed to empirically validate each design in a high-throughput manner in an environment where the dynamic RNA controllers should work. The potential of empirical selection should be further explored because the quantitative properties of RNA controllers can be modulated using well-designed in vivo selection schemes [43 ]. Emerging approaches in the development of dynamic RNA controllers will expand the repertoire of genetic parts for applications in metabolic engineering and synthetic biology.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro selection recently published work utilizing a coupled in vitro-in vivo selection strategy [43 ]. In this study, an aptamer library that binds to a flavonoid, naringenin, was cloned upstream of a dual selectable marker gene.…”
Section: Library Generationmentioning
confidence: 99%
“…Previous studies showed that modifying binding kinetics and affinity by directed mutagenesis of aptamer domains of riboswitches shifted the dose-response curves [18][19][20]. Another approach focused on modifying an expression platform, which was also effective for tuning of riboswitches [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Common biosensors in dynamic control are transcriptional riboswitches [7] and transcription factors [75]. Progress in RNA engineering has led to a growing number of riboswitches that respond to specific metabolites [66,26]. Studies have shown that RNA sequences shape the sensitivity and threshold of riboswitch dose-response curves [52,5], yet the precise tuning of riboswitch function remains a significant challenge.…”
Section: § 1 Introductionmentioning
confidence: 99%